Politics and the search for the common good - Sluga, Hans D. 1937- (Cambridge Univ. Press, 2014)
"Rethinking politics in a new vocabulary, Hans Sluga challenges the firmly held assumption that there exists a single common good which politics is meant to realize. He argues that politics is not a natural but a historical phenomenon, and not a single thing but a multiplicity of political forms and values only loosely related. He contrasts two traditions in political philosophy: a 'normative theorizing' that extends from Plato to John Rawls and a newer 'diagnostic practice' that emerged with Marx and Nietzsche and has found its three most prominent twentieth-century practitioners in Carl Schmitt, Hannah Arendt, and Michel Foucault. He then examines the sources of diagnostic political thinking, analyzes its achievements, and offers a critical assessment of its limitations. His important book will be of interest to a wide range of upper-level students and scholars in political philosophy, political theory, and the history of ideas"..
Keywords: PHILOSOPHY / Political; Philosophie; Politische Wissenschaft; Common good; Political science -- Philosophy; Gemeinwohl; Politisches Denken